(untitled) (Revista de Crítica Literaria Latinoamericana, 2012)
Around the transformations of the cultural and literary field of the last three decades of the last century, and considering the generic and disciplinary, inter artistic relationships between them, we will talk about the neo-avant garde as an expansion process of literary codes. This poetics is related to the restoration that affected the category of literary work after the vanguardist subject, creator and interpreter, inflamed of rhetoric and, in many cases, of utopia and messianism. A complex process we find in the border writings of Carmen Berenguer (Naciste pintada), Enrique Verástegui (Angelus Novus) and Nestor Perlongher (Poemas completos).